Construction and response of a highly granular scintillator-based electromagnetic calorimeter - Repond, Jose O.; Kaplan, Alexander; Schultz-Coulon, Hans-Christian (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2018)
A highly granular electromagnetic calorimeter with scintillator strip readout is being developed for future linear collider experiments. A prototype of 21.5 X0 depth and 180×180mm2 transverse dimensions was constructed, consisting of 2160 individually read out 10×45×3mm3 scintillator strips. This prototype was tested using electrons of 2-32 GeV at the Fermilab Test Beam Facility in 2009. Deviations from linear energy response were less than 1.1%, and the intrinsic energy resolution was determined to be (12.5±0.1(stat.)±0.4(syst.))%∕E[GeV]⊕(1.2±0.1(stat.)−0.7+0.6(syst.))%, where the uncertainties correspond to statistical and systematic sources, respectively.
Gesehen am 04.02.2020